Rancang Bangun Sistem Monitoring PLTS Off-Grid Pada Mobile Tower Berbasis Internet of Things - Trisuyono Suparmin; Adi Mulyadi; Widhi Winata Sakti (CV. Sekawan Siji, 2026)
This research developed and tested an Internet-of-Things-based off-grid solar power plant monitoring system on mobile towers using the Telegram platform as the monitoring medium. The objective of this research was to create an efficient and real-time mobile tower performance monitoring system based on temperature, current, power, light intensity, voltage, latency, and error percentage. The experimental method, using hardware (ESP32, RS485, LM2596) and software (Telegram) for data monitoring, was tested in the field. Testing was conducted twice on different dates, weather conditions, and for different durations. The results showed a system efficiency of 84.68%, error below 5%, accuracy of 99.54% for temperature, 98.52% for current, 98.7% for power, and 99.33% for voltage, with latency of 89-267 ms. The system was deemed to meet the criteria for a sustainable mobile tower monitoring solution.